Mancais aerostáticos porosos fabricados em compósito cimentício reforçado com nanotubos de carbono - Leandro José da Silva (2015)
The aerostatic bearings are those in which a thin film of air (gas) at high pressure is used to reduce (or eliminate) the direct contact between two surfaces in relative motion. The use of a porous material for the aerostatic bearing restrictor promotes an uniform air pressure distribution under the bearing surface. The main difficulty in the development of porous materials for this purpose is achieving proper mechanical strength and permeability, in order to make the bearing withstands high pressure air and fluid flow, respectively. This work aims to develop a test bench of aerostatic thrust bearings in order to evaluate the behaviour of cementitiuos materials as porous restrictors for this kind of bearings. The loading capacity tests of the bearing made with cementitious restrictor reinforced with silica microparticles showed an aceptable operational behaviour, besides being a low cost and easy-to-manufacture material, mainly when compared to the advanced sintered ceramics commonly used for the same purpose. Cementitious pastes reinforced with carbon nanotubes were also developed and evaluated as porous restrictors for axial aerostatic bearings. A full factorial design of experiments was used to identify the main and interaction effects of the experimental factors, such as "Superplasticiser" and "Carbon Nanotubes" inclusions on the investigated properties. The interaction between the factors "superplasticizer and carbon nanotubes" significantly affected all responses, except for the static modulus of elasticity. The superplasticizer showed a positive effect for the dispersion of carbon nanotubes in cementitious matrix. The carbon nanotubes promoted significant increasing in bulk density, compression strength, modulus of elasticity and oxygen permeability of the cementitious pastes, as a reducing for the apparent porosity, at the same time. The cementitious pastes made with 0.05%wt of carbon nanotubes and 0.4%wt of superplasticizer revealed promising physical and mechanical properties for such application, being tested as a bearing air restrictor. The cementitious material did not present acceptable permeability for the application as a single layer restrictor, however the material can be considered as a promising alternative for porous thrust bearing made with two or more layers.